The Association between Eating Traits and Weight Change after a Lifestyle Intervention in People with Type 2 Diabetes Mellitus. (3rd June 2018) - Koopman, Anitra D. M.; vd Ven, Maya; Beulens, Joline W.; Welschen, Laura M.; Elders, Petra J.; Nijpels, Giel; Rutters, Femke
Abstract : Aims . To date, studies on the role of eating traits in weight loss success have only included obese people without type 2 diabetes mellitus (T2DM), thereby disregarding negative effects of T2DM-related metabolic changes. Our aim was to assess the association between eating traits and weight change after a lifestyle intervention in people with T2DM. Methods . For the current study, we reexamined data from a six-month intervention in 120 participants. We determined eating traits at baseline, using the DEBQ, which were used to produce three groups: unsuccessful dietary restrained (high restraint, high emotional/external eating scores), successful dietary restrained (high restraint, low emotional/external eating scores), and reference (low restraint, high or low emotional/external eating scores). Linear regression was used to study the association between the eating trait groups and weight changes after six months, while correcting for possible confounders. Results . On average, the weight loss success was limited, with a third of the participants being weight stable, a third losing weight > −1 kg (average loss −2.6 ± 1.9 kg), and a third gaining weight > +1 kg (average gain +3.3 ± 1.9 kg). When compared to the reference group, the unsuccessful dietary restrained gained weight during the intervention (beta = 1.2 kg, confidence interval (CI)% = 0.1; 2). No significant change was observed in the succesful dietary restrained group. Conclusions . The eating trait of being unsuccessfully dietary restrained is associated with weight-loss failure after a six-month lifestyle intervention in people with T2DM.